Complications of proximal hypospadias repair with transverse preputial island flap urethroplasty: a 15-year experience with long-term follow-up - Wang, Chao-Xu (Asian J Androl, 2019)
There is still debate regarding the optimal surgical approach for proximal hypospadias. This retrospective study aims to evaluate the long-term outcomes using transverse preputial island flap urethroplasty. A total of 320 patients were included, with a mean follow-up of 40.2 months (range: 1–156 months). Complications were encountered in 125 patients (39.1%), including fistulas in 53 (16.6%), urethral strictures in 31 (9.7%), and diverticula in 41 (12.8%). The mean timing of presentation with a complication was 15.8 months (median: 1.7, range: 1–145), of which 79.2% were early complications and 20.8% were late complications. In all, 20.8% of the patients with complications presented after ≥1 year, and 12.8% presented after ≥5 years. Univariate analysis revealed that age at the time of surgery, flap length, and location of the urethral meatus were not correlated with complications. A stricture was present in 31.7% (13/41) of those with diverticula (P < 0.001), while late urethral diverticula were accompanied by urethral strictures in 11.1% (1/9) of cases (P = 0.213). These results indicate that transverse preputial island flap urethroplasty still has a high incidence of complications, even when performed by highly experienced physicians. Most complications of hypospadias are diagnosed within 1 year postoperatively, while fistulas and urinary strictures generally occur within 2 months and diverticula tend to be present by 1 year.